BIOTECHNOLOGICAL ASPECTS USE OF WASTE IN ECOLOGICAL SAFETY - Kharlamova, Olena; Shmandiy, Volodymyr; Rigas, Tetiana (My University, 2018)
The purpose of work was application of biotechnologies for providing of ecological safety of motor transport. Experimental researches are conducted after standard methods both in laboratory and in operating, terms. The special motor stand was used.
Keywords: Biotechnology; Wastes; Soabstok; Sorbent; Ecological Safety